2008
DOI: 10.1152/ajpendo.90289.2008
|View full text |Cite
|
Sign up to set email alerts
|

Estrous cycle variation of TRPV1-mediated cross-organ sensitization between uterus and NMDA-dependent pelvic-urethra reflex activity

Abstract: Cross-organ sensitization between the uterus and the lower urinary tract (LUT) underlies the high concurrence of pelvic pain syndrome and LUT dysfunctions, and yet the role of gonadal steroids is still unknown. We tested the hypothesis that cross-organ sensitization on pelvic-urethra reflex activity caused by uterine capsaicin instillation is estrous cycle dependent. When compared with the baseline reflex activity (1.00 +/- 0.00 spikes/stimulation), uterine capsaicin instillation significantly increased reflex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
26
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3
1

Relationship

3
7

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 81 publications
0
26
0
Order By: Relevance
“…Stimulation of TRPV1 in rat C fibres is dependent on the oestrous cycle favouring oestradiol (Peng et al 2008), and oestradiol may contribute to pain through TRPV1 regulation in the hippocampus (Wu et al 2010). It exerts classical (slow, genomic) effects on Trpv transcription (Hoenderop et al 2005) and can also directly or indirectly stimulate the TRPV1 receptor (Kumar et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Stimulation of TRPV1 in rat C fibres is dependent on the oestrous cycle favouring oestradiol (Peng et al 2008), and oestradiol may contribute to pain through TRPV1 regulation in the hippocampus (Wu et al 2010). It exerts classical (slow, genomic) effects on Trpv transcription (Hoenderop et al 2005) and can also directly or indirectly stimulate the TRPV1 receptor (Kumar et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…At the lumbosacral spinal cord, our laboratory has recently demonstrated a novel form of pain-related central sensitization, cross-organ sensitization, in which instillation of mustard oil (MO) into the descending colon could sensitize the reflex activity of the urethra (21,22). Pharmacological investigations indicated spinal NR2B subunit phosphorylation is crucial in the induction of cross-organ sensitization (19,20,23).…”
mentioning
confidence: 99%
“…At the lumbosacral spinal cord, our laboratory has recently demonstrated a novel form of neural plasticity, the spinal reflex potentiation (SRP) (48 -50, 72), in which the reflex activity of the urethra could be sensitized by the activation of capsaicinsensitive (75), mustard oil-sensitive (73), and transient receptor potential vanilloid subfamily member 1 (TRPV1)-sensitive (74) afferent fibers. Pharmacological investigations on SRP have demonstrated that, similar to other forms of neural plasticity, glutamatergic NMDA-dependent (11-14, 46, 47) ERK activation that subsequently phosphorylates the NMDA NR2B subunit (70 -73), a subunit that is presumed to be essential for Ca 2ϩ gating, to define the role of the NMDA receptor for dynamic synaptic plasticity (52,69), underlies the induction of SRP.…”
mentioning
confidence: 99%